Efficacy of vagus nerve stimulation in a young infant with early myoclonic encephalopathy associated with nonketotic hyperglycinemia - Beydoun, Ahmad; Nasreddine, Wassim; Dabbagh, Omar; Wazne, Jaafar; Arabi, Maher; Najjar, Marwan (Journal of Pediatric Neurology, 2011)
Early myoclonic encephalopathy (EME) is an epileptic encephalopathy characterized by highly refractory seizures and an overall bad prognosis. In this report, we present an infant who developed EME secondary to nonketotic hyperglycinemia. A vagus nerve stimulator inserted when the infant was 6 months and 3-weeks-old resulted in mild psychomotor improvement and in a dramatic reduction in seizure frequency documented by closed-circuit television-electroencephalography monitoring. This is the youngest infant in the literature reported so far inserted with a vagus nerve stimulator, and the results suggest that this treatment modality is safe and can be of benefit in reducing seizures associated with EME.
Keywords: Vagal nerve stimulation; early myoclonic encephalopathy; nonketotic hyperglycinemia